Chemical and toxicological characterisation of anticancer drugs in hospital and municipal wastewaters from Slovenia and Spain. (December 2016) - Isidori, Marina; Lavorgna, Margherita; Russo, Chiara; Kundi, Michael; Žegura, Bojana; Novak, Matjaž; Filipič, Metka; Mišík, Miroslav; Knasmueller, Siegfried; de Alda, Miren López; Barceló, Damià; Žonja, Božo; et al.
Abstract: Anticancer drugs are continuously released into hospital and urban wastewaters, where they, most commonly, undergo conventional treatment in wastewater treatment plants (WWTPs). Wastewaters contain complex mixtures of substances including parent compounds, their metabolites and transformation products (TPs). In this study, samples of hospital effluents and WWTP influents and effluents from Slovenia and Spain were analyzed for twenty-two selected anticancer drugs, their metabolites and transformation products. Acute and chronic toxicity tests were performed on the crustacean Ceriodaphnia dubia, genotoxicity was determined with Tradescantia and Allium cepa micronucleus (MN) assays and in vitro comet assay in zebrafish ( Danio rerio ) liver cell line (ZFL cells). Sixty of the two hundred-twenty determinations revealed detectable levels of anticancer drug residues. Among the targeted compounds, platinum based were most frequently detected (90%). Furthermore, erlotinib was detected in 80%, cyclophosphamide and tamoxifen in 70% and methotrexate in 60% of the samples. Seven of ten samples were toxic to C. dubia after acute exposure, whereas after chronic exposure all samples reduced reproduction of C. dubia at high sample dilutions. Allium cepa proved insensitive to the potential genotoxicity of the tested samples, while in Tradescantia increased MN frequencies were induced by a hospital effluent and WWTP influents. In ZFL comet assay all but one sample induced a significant increase of DNA strand breaks. Correlations of chemotherapeutics or their TPs were detected for all bioassays except for Allium cepa genotoxicity test, however for each test the highest correlations were found for different substances indicating differential sensitivities of the test organisms. Graphical abstract: Highlights: Hospital and municipal wastewaters contain anticancer drug residues > LOD. Hospital and municipal wastewaters are toxic and inhibit reproduction of C. dubia . In Tradescantia and in zebrafish liver cells genotoxic effects were found. Eco/genotoxicity does not correlate with the total burden with anticancer drug residues. Abstract : Could the input of anticancer drug residues into aquatic systems at measured concentrations affect the environment?